1998
DOI: 10.1097/00006534-199811000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Locally Administered Vascular Endothelial Growth Factor cDNA Increases Survival of Ischemic Experimental Skin Flaps

Abstract: Microvascular surgery has emerged as an attractive area for recent advances in the field of gene therapy. The present study investigated the survival of ischemic, experimental skin flaps after treatment with the gene encoding vascular endothelial growth factor (VEGF). In 30 Sprague-Dawley rats, anterior abdominal skin flaps supplied by the epigastric artery and vein were created. Ten animals were treated with a mixture of liposomes and the cDNA encoding the 121-amino acid isoform of VEGF. Another 10 animals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 4 publications
3
60
0
1
Order By: Relevance
“…Surprisingly, in these mice the prominent GFP expressing cell type appeared to be the fibroblast, which stands in contrast to a keratinocyte dominated VEGF expression other groups have reported previously (Frank et al 1995). A cutaneous study on intra-arterial liposomal gene transfer to experimental skin flaps prior to exposure to ischaemia revealed an increased tissue viability after treatment with VEGF expression vector cDNA in correlation with increased VEGF protein expression (Taub et al 1998). The angiopoietins form a second family of growth factors essential for the regulation of vascular development (Holash et al 1999).…”
Section: Angiogenic Growth Factorsmentioning
confidence: 62%
“…Surprisingly, in these mice the prominent GFP expressing cell type appeared to be the fibroblast, which stands in contrast to a keratinocyte dominated VEGF expression other groups have reported previously (Frank et al 1995). A cutaneous study on intra-arterial liposomal gene transfer to experimental skin flaps prior to exposure to ischaemia revealed an increased tissue viability after treatment with VEGF expression vector cDNA in correlation with increased VEGF protein expression (Taub et al 1998). The angiopoietins form a second family of growth factors essential for the regulation of vascular development (Holash et al 1999).…”
Section: Angiogenic Growth Factorsmentioning
confidence: 62%
“…[34][35][36][37] The benefits of enhanced angiogenesis have primarily been shown in models of impaired wound healing 28,32,33 or severe injury. [29][30][31] In contrast, several reports have shown that modulation of angiogenesis does not affect epidermal healing rates or overall wound closure to a great degree, [38][39][40][41][42][43] and some studies have even reported enhanced healing with reduced angiogenesis. 44 Thus, although there are many studies examining angiogenesis and wound repair, the degree to which angiogenesis actually facilitates healing under normal circumstances is still not known.…”
Section: Discussionmentioning
confidence: 96%
“…It is not surprising then, that many studies have found angiogenesis to be beneficial for wound repair. Stimulation of angiogenesis can enhance healing rates, [27][28][29][30][31][32][33] whereas a reduction in angiogenesis can impair the same. [34][35][36][37] The benefits of enhanced angiogenesis have primarily been shown in models of impaired wound healing 28,32,33 or severe injury.…”
Section: Discussionmentioning
confidence: 99%
“…52 The site of VEGF delivery may not have been optimal, since a separate study revealed that intravascular delivery of naked DNA encoding VEGF improved the survival of skin flaps containing vessels arising from a single artery. 53 It is worth noting that in the clinic it is seldom that flaps are vascularized in this manner.…”
Section: Figure 7 Histology At Day 7 After Implantation Showing the Imentioning
confidence: 99%